Faktor-faktor yang Mempengaruhi Praktik-praktik Pengungkapan Sosial: Studi pada Perusahaan-perusahaan High Profil yang Terdaftar di Bursa Efek Jakarta - Pratiwi, Maharani Suendaryanti; Djamhuri, Ali (TEMA, 2004)
The purposes of this study are to find out whether corporate size, profitability, and public share ownership influence social disclosure practices in annual report; and to find out which one of those independent variables give the most effect on social disclosure practice in annual report. Using 102 annual reports 2002 of high-profile corporates listed in Jakarta Stock Exchange, this study found that corporate size, profitability, and public share ownership give a significant effect to social disclosure practices in annual report in a simultaneous way. But in partial way, only corporate size gives a significant effect to social disclosure practice in annual report.Keywords: social disclosure, corporate size, profitability, and public share ownership.